2012
DOI: 10.1590/s1982-56762012005000001
|View full text |Cite
|
Sign up to set email alerts
|

First record of Tomato chlorotic spot virus in the USA

Abstract: A tospovirus was identified in tomato plants from two counties in Florida by reverse transcription-PCR and sequencing of portions of the S, M and L genomic segments. The predicted amino-acid sequences of the N protein of PCR products from four plant samples were >96% identical to those of TCSV. Partial nucleic acid sequences of the L and M RNA were >97% identical to those reported for TCSV isolates. Extracts from field samples infected test plants and produced symptoms similar to those reported for TCSV. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 13 publications
0
21
0
6
Order By: Relevance
“…2 ). Pairwise comparisons of the N, NSs and RdRp protein sequences showed that TCSV-DR is most closely related to the TCSV isolates reported in cultivated and ornamental plants [ 17 , 18 ]. The NSm and the glycoprotein precursor protein sequences analysis revealed TCSV-DR closest to the unique reassortant isolate formed between TCSV and GRSV (S GRSV , M TCSV and L GRSV ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Pairwise comparisons of the N, NSs and RdRp protein sequences showed that TCSV-DR is most closely related to the TCSV isolates reported in cultivated and ornamental plants [ 17 , 18 ]. The NSm and the glycoprotein precursor protein sequences analysis revealed TCSV-DR closest to the unique reassortant isolate formed between TCSV and GRSV (S GRSV , M TCSV and L GRSV ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Melon yellow spot virus (MYSV), formerly reported only in Asia, has for the first time been found outside Asia, in Ecuador (94). Furthermore, in Florida in 2012 (66), the first occurrence of a natural interspecific reassortant Groundnut ringspot virus (GRSV)-Tomato chlorotic spot virus (TCSV) in tomato fields has been reported (144) and its parental TCSV species identified. Another study performed with a number of TSWV isolates showed that reassortment among isolates within a species seems to be a common evolutionary strategy (136), and, in one case, a resistance-breaking (RB) isolate was shown to originate through reassortment (73).…”
Section: Tospovirus Diversity: New and Old Threats To Vegetable Cropsmentioning
confidence: 99%
“…Subsequently, TCSV was isolated from sweet peppers, potatoes, endives, celery, lisianthus and various weeds with mosaic, necrosis, chlorotic or stunting symptoms in Argentina and Brazil (Boiteux et al ., ; Gracia et al ., ; Colariccio et al ., ; Dal Bio et al ., ; Eiras et al ., ), and from outbreaks on lettuce and gilo in Brazil (Colariccio et al ., ; Rabelo et al ., ). In the USA, TCSV was first detected from tomatoes in south Florida in 2012 (Londoño et al ., ), and then from lettuce, impatiens and peppers (Webster et al ., ). In Puerto Rico, TCSV was also found from tomatoes, peppers, jimsonweed ( Datura stramonium ), and lettuce in 2013 (Estévez de Jensen et al ., ; Estévez de Jensen & Adkins, ).…”
Section: Current Global Status Of the Viruses Transmitted By F Occidmentioning
confidence: 99%